Secondary settlement estimation in surcharge preload subject to time effect of secondary consolidation coefficient - Hu, Ya-yuan; Yang, Ping (Journal of Central South University, 2017)
In order to eliminate the settlement underestimation in surcharge preload engineering, a study based on Bjerrum’s creep diagram and the tangent slope definition of secondary consolidation coefficient was carried out to analyze the time effect of secondary consolidation coefficient of over consolidated soil, and a time–growth model for it was formulated. As Bjerrum’s creep diagram is an idealized model, oedometer tests were performed to improve the above time–growth model of secondary consolidation coefficient for the purpose of achieving a better agreement with the actual ground situations. It is found that secondary consolidation coefficient of over consolidated soil not only decreases with the ratio of historical maximum to current effective stress of soil (OCR), but also increases with the development time of secondary consolidation. No matter how large OCR is, the long-term time effect of secondary consolidation coefficient of over consolidated soil is all significant. Based on the above results, a model for settlement estimation was formulated and a case study to estimate it indicates that the settlement estimated by our method is 2–5 times larger than that estimated by the previous method. Moreover, the larger the OCR is as well as the longer the service life is, the larger the difference between our method and the previous method is. Thus, the post-construction secondary settlement in surcharge preload engineering will be underestimated when neglecting the time effect of secondary consolidation coefficient in over consolidated state.